Biochemical and Sensory Characteristics of the Smoked African Catfish (Clarias gariepinus) under Different Storage Conditions in the Coastal Region of Kenya - Obiero, Maurice O.; Oduor-Odote, Peter M.; Ruwa, Raymond; Omega, Maurice (Kenya Aquatica Journal, 2018)
Smoking is one of the oldest methods of drying food for purposes of preservation and flavouring. However, technologies are changing fast resulting in various smoking techniques to improve fish quality and shelf life. Different storage conditions have been used and others are still being tested to improve shelf life of smoked fish products. The aim of this study was to determine the changes in biochemical and sensory attributes of smoked African catfish (Clarias gariepinus) under different storage conditions. Samples were stored in open air, sealed polythene paper bags and vacuum sealed polythene paper bags for a period of 30 days. Storage in open air exhibited highest value at day 30 while vacuum package exhibited the least. Protein decreased with time to lowest value of 60.83% in the open air storage at day 30 while those of vacuum packaging exhibited insignificant change with time. Fat content showed no significant linear change with storage time except the one stored under normal packaging. Ash and moisture content exhibited linear change with time on open package samples only. Organoleptic responses remained constant until day 30 when there was a slight change in responses on taste and overall acceptability. In general, pronounced changes were exhibited on open air while vacuum packaging had the least changes.
Keywords: Smoking; Shelf life; Organoleptic; Kilns; Packaging; Quality